Biodiversity and Evolutionary Ecology of Extinct Organisms - Bose, Rituparna. (Springer Theses, Recognizing Outstanding Ph.D. Research, 2013)
Increasing rate of species extinction in the present day will lead to a huge biodiversity crisis; eventually, this will lead to the paucity of non-renewable resources of energy making our Earth unsustainable in future. To save our mother planet from this crisis, studies need to be performed to discover abundant new fossil sites on Earth for continued access to oil-rich locations. Most importantly, a holistic approach is necessary in solving the present problem of biodiversity loss. This book presents newly developed quantitative models in understanding the biodiversity, evolution and ecology of extinct organisms. This will assist future earth scientists in understanding the natural and anthropogenic causes behind biodiversity crisis and ecosystem collapse. In addition, this study can be of great interest to exploration geologists and geophysicists in potentially unraveling natural resources from our sustainable Earth.